TEACHING METHODS IN THE THEORY OF GENERAL DIDACTICS AND DIDACTICS OF TECHNICAL SUBJECTS - KROPÁČ, Jiří; PLISCHKE, Jitka (Trends in education, 2014)
The paper is aimed at the differences between the presentation of teaching methods, especially their classification, in general didactics and branch didactics of technical subjects. It is noted, that the rate of the application of teaching methods for technical subjects is low. Further are considered reasons and connections of this fact.
Keywords: teaching methods; classification of teaching methods; general didactics; branch didactics.